2021
DOI: 10.1186/s12888-021-03537-z
|View full text |Cite
|
Sign up to set email alerts
|

Mental disorders pattern in staff of a military unit in Iran: the role of metabolic syndrome on latent class membership

Abstract: Introduction Mental disorders are among the most prevalent health problems of the adult population in the world. This study aimed to identify the subgroups of staff based on mental disorders and assess the independent role of metabolic syndrome (MetS) on the membership of participants in each latent class. Methods This cross-sectional study was conducted among 694 staff of a military unit in Tehran in 2017. All staff of this military unit was invit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…Using the fitted LCA model, each individual in the study sample is then probabilistically assigned to a class based on their observed data, resulting in subgroups of individuals who are most similar to each other and different from individuals in the other subgroups. [24][25][26] We fit the LCA model 3 times varying the number of classes from 2 to 4 and included only the substance use variables in the models. To select the best model among the three models, we compared the likelihood-ratio statistic G 2 , the Akaike information criteria (AIC), the Bayesian information criterion (BIC), and Entropy.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Using the fitted LCA model, each individual in the study sample is then probabilistically assigned to a class based on their observed data, resulting in subgroups of individuals who are most similar to each other and different from individuals in the other subgroups. [24][25][26] We fit the LCA model 3 times varying the number of classes from 2 to 4 and included only the substance use variables in the models. To select the best model among the three models, we compared the likelihood-ratio statistic G 2 , the Akaike information criteria (AIC), the Bayesian information criterion (BIC), and Entropy.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to considering model fit statistics, we also considered the interpretability of the models. 23,25,26 After identifying the substance use clusters using our final LCA model, we calculated the prevalence of sociodemographic and behavioral health characteristics in each substance use cluster. We then used modified Poisson regression to calculated adjusted prevalence ratios (aPRs) and corresponding 95% confidence intervals to statistically test for differences in prevalence of behavioral health characteristics (modeled as the outcome) between the clusters (modeled as the exposure) while adjusting for maternal age, neighborhood deprivation index (reference = 1st quartile), race/ethnicity (reference = non-Hispanic White), and parity (reference = 1 or more).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations